Conformational relaxations of human serum albumin studied by molecular dynamics simulations with pressure jumps - Yesylevskyy, S.O.; Hushcha, T.O. (Вiopolymers and Cell, 2012)
Aim. In this work we developed a novel technique of obtaining the spectrum of conformational relaxations in a solvated protein using non-equilibrium molecular dynamics simulation. Methods. Structural relaxations in the protein are initiated by the abrupt jump of pressure in the NPT simulations. The change of the protein volume after the jump is monitored and the Maximum Entropy Method is used for spectral decomposition of the volume relaxation curve. The human serum albumin (HSA) is used as a test case. Results. The obtained relaxation spectrum of HSA contains one component attributed to the bulk water and five components caused by the relaxations of the protein globule and its hydration shell. All relaxation components are in good agreement with the available experimental data obtained by the time-resolved spectroscopy and the broadband acoustic spectroscopy of HSA. Conclusions. The developed technique allows obtaining spectra of conformational relaxations of soluble proteins in a range of time scales from ~0.1 ps to ~50 ns utilizing single non-equilibrium molecular dynamics simulation. Keywords: protein relaxations, molecular dynamics, maximum entropy method, pressure jump, HSA.